Outbreak of Botulism Due to Illicit Prison-Brewed Alcohol: Public Health Response to a Serious and Recurrent Problem. (27th December 2017) - Rao, Agam K; Walters, Maroya; Hall, Julia; Guymon, Colleen; Garden, Richard; Sturdy, Pauline; Thurston, Diana; Smith, Lori; Dimond, Melissa; Vitek, Dagmar; Bogdanow, Linda; Hill, Mary; et al.
Abstract : We report an outbreak of botulism in a US prison. The public health response to this outbreak highlights challenges unique to this recurrent problem. Lessons learned may facilitate future investigations. Abstract: Background: Botulism is a rare, sometimes lethal neuroparalytic illness. On 2 October 2011, an inmate at prison A developed symptoms compatible with botulism after drinking pruno, an illicit, prison-brewed alcoholic beverage. Additional illnesses were identified within several days. We conducted an investigation to determine the cause and extent of the outbreak. Methods: A case was defined as signs or symptoms of botulism in a prison A inmate with onset during 30 September–9 October 2011. Cases were identified through medical evaluations and interviews with inmates about recent pruno consumption. Laboratory testing was performed for Clostridium botulinum and botulinum neurotoxin. Ingredients, preparation, and sharing of the implicated pruno were investigated. Results: Eight prisoners developed botulism; all drank pruno made with a potato. Three received mechanical ventilation. Culture of fluid from a sock that inmates reported using to filter the implicated pruno yielded C. botulinum type A. The implicated batch may have been shared between cells during delivery of meal trays. Challenges of the investigation included identifying affected inmates, overcoming inaccuracies in histories, and determining how the illicit beverage was shared. Costs to taxpayers were nearly $500000 in hospital costs alone. Conclusions: Pruno made with potato has emerged as an important cause of botulism in the United States. This public health response illustrates the difficulties of investigating botulism in correctional facilities and lessons learned for future investigations.